METODE PEMBELAJARAN PENDIDIKAN DALAM PERSPEKTIF ALQUR’AN (Surah An-Nahl Ayat 125) - Kamaruddin Kamaruddin (AL-ILMU, 2022)
In conveying the treatise, the Prophet Muhammad obtained a very valuable guide, namely in the form of basic principles in the method of conveying Islamic teaching material listed in Surah An-Nahl verse 125. This verse contains the principles of preaching (teaching, educating) which consists of Al-Hikmah (wisdom-wisdom sourced from the Qur'an), Maudzah Hasanah (kind words, gentle) and Mujlah (discussion, dialogue if necessary to argue). da'wah, communication, public relations, education and other matters related to human interaction. Education as a part of da'wah, which is to invite people to do good and prevent evil, cannot be separated from the use of some of the principles mentioned above. So that students can gain knowledge and there is a change in behavior that is expected from each process of teaching and learning activities.